Post-Traumatic Stress Symptoms and Their Correction Through Remote Rehabilitation in Patients with Post-COVID Syndrome During the War - Burdeinyi, Андрій; Chaban, Олег (Psychosomatic Medicine and General Practice, 2024)
Relevance. The COVID-19 pandemic has caused not only physical but also significant psycho-emotional consequences, leading to the development of post-COVID syndrome, which includes anxiety, depressive states, and symptoms of post-traumatic stress disorder (PTSD). The high level of uncertainty during the pandemic, fear for one's own life and that of loved ones, isolation, and prolonged treatment without clear pharmacological countermeasures created conditions for the formation of psychotraumatic consequences even among those without prior traumatic experiences. Additional pressure caused by the war compounds the existing post-COVID syndrome, intensifying psychotraumatic burdens due to losses, constant stress, and forced displacement. In such conditions, post-traumatic stress becomes not only an individual issue but also a social phenomenon, requiring a comprehensive approach to diagnostics, treatment, and the development of systemic rehabilitation programs. This highlights the importance of creating modern, integrated medical and psychological care methods adapted to wartime conditions and utilizing remote interaction technologies. Objective. To investigate the effectiveness of the “Medical and Psychological Rehabilitation Program for Anxiety and Depressive Post-COVID Disorders in Remote Interaction Settings” among patients with anxiety and depressive post-COVID disorders during wartime in Ukraine by assessing the dynamics of post-traumatic stress levels. Materials and Methods. The study involved 240 individuals with depressive and anxiety post-COVID disorders, adhering to ethical and deontological standards in accordance with the principles outlined in the Declaration of Helsinki. The primary diagnostic tools for identifying post-traumatic stress included clinical interviews, assessment of PTSD criteria based on DSM-5, and the PTSD Checklist for DSM-5 (PCL-5). Results. At the beginning of the study, the average PCL-5 scores for post-traumatic stress symptoms were almost identical in the study group and the control group, at 30.42±17.866 and 29.822±16.574, respectively (t=-0.271; p=0.786). By day 63, the average score in the study group had decreased to 13.295±8.728, with the PTSD symptom complex reduced in 5 out of 57 participants. In the control group, the average score remained nearly unchanged at 29.178±13.542, with the number of participants exhibiting PTSD symptoms decreasing from 54 to 44 (p<0.001; t=10.836). After three months, the average score in the study group further decreased to 3.443±2.709, while in the control group, it decreased to 24.347±13.214. The PTSD symptom complex in the study group dropped to zero, whereas in the control group, it increased from 44 to 47 (p<0.001; t=17.108). Conclusions. The study results confirm the effectiveness of the medical and psychological rehabilitation program for patients with post-COVID anxiety and depressive disorders in remote interaction settings, particularly in reducing the PTSD symptom complex arising from both post-COVID syndrome and the impact of the war in Ukraine. These findings enable the adaptation of treatment processes through telemedicine and telepsychology, expanding the possibilities for medical and psychological care and rehabilitation via remote interaction.